Biochemical and immunological characterization of mutant L-M cells with altered levels of dibutyryl cyclic AMP-inducible alkaline phosphatase. - Gum, J R (1985)
Phosphotyrosine-Sepharose 4B was synthesized and used to purify L-cell alkaline phosphatase. Antibodies to this enzyme interacted with the alkaline phosphatase of strains A-1-2 and A-3-3, mutants that express the enzyme constitutively. This and thermal stability studies suggest that these mutants contain the same alkaline phosphatase isozyme as their parent strain.